Is economics coursework, or majoring in economics, associated with different civic behaviors? - Sam Allgood; William Bosshardt; Wilbert van der Klaauw; Michael Watts (Federal Reserve Bank of New York, 2010)
Studies regularly link levels of educational attainment to civic behavior and attitudes, but only a few investigate the role played by specific coursework. Using data collected from students who attended one of four public universities in our study, we investigate the relationship between economics coursework and civic behavior after graduation. Drawing from large samples of students in economics, business, or general majors, we compare responses across the three groups and by the number of undergraduate economics courses completed. We find that undergraduate coursework in economics is strongly associated with political party affiliation and with donations to candidates or parties, but not with the decision to vote or not vote. Nor is studying economics correlated with the likelihood (or intensity of) volunteerism. While we find that the civic behavior of economics majors and business majors is similar, it appears that business majors are less likely than general majors to engage in time-consuming behaviors such as voting and volunteering. Finally, we extend earlier studies that address the link between economics coursework and attitudes on public policy issues, finding that graduates who studied more economics usually reported attitudes closer to those expressed in national surveys of U.S. economists. Interestingly, we find the public policy attitudes of business majors to be more like those of general majors than of economics majors.
Keywords: A22; A13; D71; 330; Economics training; civic behaviors